THE EFFECTIVENESS OF MOTIVATION AND SATISFACTION ON TEACHER PERFORMANCE THROUGH DISCIPLINE AS INTERVENING VARIABLES - Anggih Perian Guswan Putra; Agus Iwan Mulyanto (JURNAL ILMIAH ILMU ADMINISTRASI, 2021)
This study aims to determine the effectiveness of work motivation and job satisfaction on the performance of educators through work discipline as an intervening variable. The type of research is explanatory, the data collection technique is interviews with guiding questions and questionnaires, the sampling technique is the census method with non-probability sampling, the number of samples is 47 educators in the production department. Data were analyzed through SPSS software. The results and discussion show that there is an effective work motivation on work discipline with a value of t count > t table, Effective job satisfaction on work discipline with a value of t count > t table, Effective work motivation and job satisfaction on work discipline with a value of F count. Medium, based on the Sobel test, effective work motivation of educators' performance through work discipline, has a t count > t table, and effective job satisfaction, educator performance through work discipline, has a t count > t table. Keywords : motivation, satisfaction, discipline, educator performance, intervening